Det endelig ordforråd - Holmboe, Henrik (HERMES - Journal of Language and Communication in Business, 1992)
Text analysis and text comprehension are problems closely connected with the question of vocabulary. The vocabulary comprises the units which text analysis cannot ignore as one of its goals, and text comprehension - irrespective of theoretical inclination - will always interact with word comprehension. You may claim that texts presuppose words and word semantics in so far as the words are the bricks in the building of texts, or you may claim that the meaning of words is an abstract concept presupposing the sentence, or the text, and not having its empirical status; but to the best of my knowledge nobody will claim that there is no interrelation between the comprehension of words and that of texts. Thus it is relevant to study the words and the vocabularies of languages considering i.a., whether the vocabulary is finite or infinite. This paper will argue the first case, even for a language like Danish with its wide range of word formation potentials which might present the latter case as the attractive alternative. The arguments will be based on facts about the structure of the words and on some considerations on functional and semantic load. The paper is a slightly revised and extended version of a oral contribution given at a conference "Danish Text Analysis on Computers" in November 1991 at the University of Copenhagen under the auspices of the Danish Research Council for the Humanities.